1992
DOI: 10.1029/91tc01039
|View full text |Cite
|
Sign up to set email alerts
|

Some thermomechanical aspects of the subduction of continental lithosphere

Abstract: On the basis of thermal and mechanical modeling, it is concluded that the subduction of continental lithosphere can lead to its breakup and the formation of a new plate contact within the middle or lower crust. As a result, (part of) the subducting continental crust is transferred to the upper plate. Breakup is caused by the resistive forces acting upon subducting continental crust, due to the buoyancy of crustal material and to friction at the plate contact, as well as the decrease in strength of the subducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 52 publications
2
28
2
Order By: Relevance
“…However, the eclogitized granulites are associated with Precambrian gabbros, anorthosites and peridotites (Tucker et al, 1991). In both cases, garnet peridotites are associated with continental rocks and their exhumation is explained by decoupling of the continental slice from the descending oceanic lithosphere due to the positive buoyancy of sialic continental rocks within the subduction channel (Van der Beuckel, 1992;Ernst, 1999Ernst, , 2005. If this hypothesis is confi rmed, it reinforces the idea that only the upper crust is exhumed.…”
Section: Continental-type Subductionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, the eclogitized granulites are associated with Precambrian gabbros, anorthosites and peridotites (Tucker et al, 1991). In both cases, garnet peridotites are associated with continental rocks and their exhumation is explained by decoupling of the continental slice from the descending oceanic lithosphere due to the positive buoyancy of sialic continental rocks within the subduction channel (Van der Beuckel, 1992;Ernst, 1999Ernst, , 2005. If this hypothesis is confi rmed, it reinforces the idea that only the upper crust is exhumed.…”
Section: Continental-type Subductionmentioning
confidence: 59%
“…Furthermore, sialic crustal rocks remain buoyant during subduction because their density is not signifi cantly modifi ed during subduction. 12d) (Van der Beuckel, 1992;Davies and von Blanckenburg, 1995). Decoupling of a crustal slice from the descending slab requires the buoyancy forces exceeding the strength of the upper crust, which may occur at a depth of 90 to 140 km (Fig.…”
Section: Major Driving Forces For the Exhumationmentioning
confidence: 99%
“…Importantly, Carry et al. (2009), along with the earlier work of den Beukel (1992), showed that thermal weakening of the slab top is a critical control on when detachment occurs.…”
Section: Discussionmentioning
confidence: 83%
“…1. Extension forces in the slab eventually result in slab break‐off, when they are large enough to overcome the strength of the entire subducting slab [ van den Beukel , 1992; Davies and von Blanckenburg , 1995; Yoshioka and Wortel , 1995; Wong A Ton and Wortel , 1997]. Published numerical simulations show that slab detachment is expected to occur following subduction and during the early stages of continental collision.…”
Section: Laboratory Experimentsmentioning
confidence: 99%